Tropical leg ulcers in children: more than yaws. (April 2016) - Fegan, David; Glennon, Mary Jacqueline; Kool, Jacob; Taleo, Fasihah
The management of yaws has changed in recent years. Mass treatment with oral azithromycin has replaced intramuscular benzathine benzylpenicillin. Treponemal and non-treponemal serology (equivalent to TPHA and RPR) point-of-care blood testing is now available. In addition, recent studies in yaws endemic regions have shown that a significant number of leg ulcers in children which are clinically suggestive of yaws are caused by Haemophilus ducreyi. It is noteworthy that the World Health Organization has also set the ambitious goal to eliminate yaws by 2020.